Mobile phones & behavioral modalities: Surveying users' practices - Stylios, Ioannis Chr; Chatzis, Sotirios P.; Thanou, Olga; Kokolakis, Spyros A. (My University, 2016)
Mobile phones are one of the most popular means of access to the internet. Users, via the telephone, connect to different services such as: Google, social networks, work accounts, banks accounts, etc. Those services, are many times, left open in their device. This enables risks, such as, loss or/and the violation of their personal data. In addition, in case of device theft after login, full access to sensitive data and applications may be fully granted. The purpose of this research is to analyze the most salient patterns characterizing user practices regarding certain behavioral modalities including: the way of using the various applications, power consumption, touch gestures and guest users' habits. To this end, we used an original questionnaire, created for the needs of the specific survey, to examine whether we can find some trends among the users. This can give us a qualitative information, for the different behaviors / "characters" of users, in order to be used in further research regarding User's Continuous Authentication.
Keywords: Behavioral Modalities; Continuous Authentication; Mobile Phones; Survey